Legal Analysis of Transfer of Land Ownership Rights Based on Court Decisions at the Jayapura City Land Office - Rongalaha, Johan; Palenewen, James Yoseph (PT. Riset Press International, 2025)
Transferring land ownership rights based on court decisions is significant so that the parties have a clear legal status and can guarantee legal certainty. This study aims to determine the process of transferring land ownership rights based on court decisions and the obstacles faced in transferring land ownership rights based on court decisions at the Jayapura City Land Office. The method used in this study is normative and empirical; normative juridical is an approach that refers to laws, literature, and written regulations and sees the reality that occurs in the field. The results of this study reveal that the process of transferring land ownership rights based on court decisions at the Jayapura City Land Office still relies on applicable laws and regulations, including the provisions of Government Regulation Number 24 of 1997 concerning Land Registration, PMNA/KBPN Number 3 of 1997 concerning Provisions for Implementing PP Number 24 of 1997, Changes in Rights based on Court Decisions Government Regulation No. 24 of 1997 Article 55 and Law Number 4 of 2004 concerning Judicial Power. Meanwhile, the obstacles faced in the process of transferring land ownership rights based on court decisions at the Jayapura City Land Office are the lack of completeness of files from the Applicant, who is forced by the counter officer who checks and finds the files are lacking and then returns them to the Applicant. The Applicant also complains about the high cost of paying BPHTB at the Jayapura City Regional Revenue Office, in addition to the lack of public knowledge in the process and flow of administration at the Land Office, where the online checking process must be carried out first by a Notary/PPAT.